The influence of the team games tournament learning model assisted with the PhET application on increasing mathematic concepts of elementary school students - Putri, Sarah Anida; Rohimah, Siti Maryam; Nurhadi, Mohd. (Desimal: Jurnal Matematika, 2025)
This research is motivated by students' limited ability to understand mathematical concepts, the lack of diverse instructional media, the predominance of conventional teaching methods, and students' diminished motivation and interest in mathematics, particularly in solving word problems. This research aims to explore the learning process, student achievements, improvements, and the impact of implementing the Team Games Tournament (TGT) teaching approach supported with the PhET application on students' understanding of mathematical concepts in mathematics. A quasi-experimental method was employed with a nonequivalent control group design. Data collection methods included pretests (before instruction) and posttests (after instruction). Data analysis was carried out using normality, homogeneity, and hypothesis testing through t-tests and the Mann-Whitney U test. The findings reveal that the learning process when using the TGT teaching approach supported by the PhET application proceeded effectively. From the hypothesis testing results, analysis revealed a meaningful difference between the pre-test scores of the control and experimental classes, together with a substantial difference in post-test scores. This demonstrates that students' ability to comprehend mathematical concepts improved both before and after using the TGT teaching approach with PhET assistance. An effect size test showed a result that falls within the large category. Hence, the application of the TGT teaching approach, supported by the PhET application, positively influences students' ability to understand mathematical concepts.